Strength analysis of composite envelope structures considering the tension–shear coupling and cutting pattern effect. (November 2022) - Chen, Longlong; Chen, Wujun; Gao, Chengjun; Li, Shiping; Song, Yinbo; Zhao, Haitao; Hu, Jianhui; Zhao, Bing
Abstract: Various strength criteria have been extensively used in the structural design of stratospheric airships. However, it is still a critical challenge to accurately predict the failure strength for ensuring structural safety due to the complex mechanical behaviors of multi-layer composite envelope materials under various loading environments. This article thus aims to establish refined numerical models for the strength prediction of envelope structures. Firstly, the mechanical properties of envelope materials were tested and investigated comprehensively. The creative concept of tension–shear​ coupling is demonstrated by the shear constitutive relation and failure criterion. Secondly, with consideration of the cutting pattern effect originating from the manufacturing procedure, a new equal-diameter flattening method for cutting gores is proposed. Finally, inflation-bursting tests of spherical and ellipsoidal envelopes were conducted to validate the proposed refined numerical models. The maximum deviation of strengths predicted by the novel criterion is less than 8% for both envelope structures, indicating that the tension–shear effect plays a significant role in the failure mechanism of flexible thin-walled envelope structures. Highlights: Tension–shear coupling is introduced in constitutive relation and failure criterion. A new equal-diameter flattening method for cutting pieces is proposed. Refined numerical models of envelope structures are built. The simulation strength is consistent with the results of inflation tests.